Distribution of Hepatitis C Virus (HCV) Genotypes Among Intravenous Drug and Non-Drug User Patients - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2021)
Genotype distribution of hepatitis C virus (HCV) can vary over the years between different patient groups and regions. The prevalence of intravenous drug users (IVDU) is known to increase in our country, yet there are a limited number of studies investigating the distribution of HCV genotypes in this group. These data are essential for monitorization of the changes in HCV epidemiology. The present study aimed to evaluate the five-year results of HCV genotyping among patients infected with HCV related to IVDU and unrelated to drug use. Plasma samples of 720 patients (HCV antibody, HCV RNA positive), which were sent to our laboratory for HCV genotyping between January 2014-March 2019 were analyzed. HCV RNA extraction from plasma samples was performed in the automated-extraction system of EZ1 advanced (Qiagen, Germany) using the EZ1 virus mini kit v2.0 (Qiagen, Germany). Amplicons were obtained by amplifying the 5'NCR and core gene region in the Rotorgene 6000 real-time PCR (Qiagen, Germany) device with the HCV RNA real-time quantitative 2.0 (NLM, Italy) kit. For the genotyping, a commercial line probe assay (LIPA) based on in vitro reverse hybridization GEN-C2.0 kit (NLM, Italy) which can distinguish 1, 2, 3, 4, 6 genotypes and 1a, 1b, 2a/c, 2b, 3a, 3b, 3c, 3k, 4a, 4b, 4c/d, 4e, 4f, 4h, 5a, 6a/b, 6g, 6f/q, 6m, 7a subtypes of HCV, based on variations in the 5'-NCR and core regions was used. HCV genotype distribution of 266 IVDU (93.2%: male; median age: 25 +/- 6.82) and 454 non-drug users (51.3%: male; median age: 56.5 +/- 16.06) were examined. In order of frequency in the group with IVDU; genotype 1a, 3a, 1b, 4c/d, 2b, 4, 3 were observed and genotype 1, 2a/c and mixed genotype (1+3a) were detected in one patient. In the group without IVDU, in order of frequency; genotype 1b, 1a, 3a, 1, 2a/c, 4 were observed and genotype 2b, 4c/d, 5a, 6a/b, 6 and mixed genotype (3+4) were detected in one patient. Genotypes la and 3a were significantly higher in the IVDU group (p< 0.00001, p< 0.00001), while 1b was significantly higher in patients without IVDU (p< 0.00001). Genotypes 1a and 3a were more common in young men (p< 0.00001, p= 0.000163), while 1b was higher in middle-aged women (p< 0.00001). The incidence of genotypes 1b (p= 0.021) and 3a (p= 0.012) was higher in foreign nationals than the Turkish patients. When the HCV genotype distribution was examined by years, it was observed that the percentages of genotype 1b and la were decreasing, while the percentage of genotype 3a was increasing. As a result, in this study, HCV genotype distribution among IVDU was observed to be different from the general population without IVDU. It was found that genotypes la and 3a were more common in the IVDU group. As in the other regions of our country, genotype 1b was found most frequently in the general population. Genotype 3a increases significantly compared to years. In our study, the determination of genotypes existing in different parts of the world may be due to the foreign nationals living in our city and our region is a tourism center. It is also necessary to investigate whether there is an increase in IVDU over the years.
Keywords: intravenous drug users; hepatitis C virus; HCV genotype; REGION; INFECTION; PROVINCE; TURKEY; EPIDEMIOLOGY; PREVALENCE; ISTANBUL; SUBTYPES; ANTALYA; PEOPLE